Reader's digest select edition : blue heaven / revelation / nothing to lose / lottery - Box, C. J.; Sansom, C. J.; Child, Lee; Wood, Patricia (Sydney, Reader's digest, 2006)
Summary: The Reader's Digest Select Editions[1] are a series of hardcover fiction anthology books, published bi-monthly and available by subscription, from Reader's Digest. Each volume consists of four or five current bestselling novels selected by Digest editors and abridged (or "condensed") to shorter form to accommodate the anthology format.
Donated by: Student
Keywords: fiction -- Four fiction story -- condensed books -- mysteries -- detective -- love story